Changes in plasma biochemical parameters following the consumption of aluminum and lead salts in rabbit - Samad Akbarzadeh; Mohsen Ani; Ali Movahed (Iranian South Medical Journal, 2008)
Background: Consumption of abundantly accessible metals like aluminum and lead or their salts can cause a wide range of diseases. As plasma biochemical parameters including VLDL, LDL-cholesterol, HDL-cholesterol, total cholesterol, triglycerides, sodium, potassium, urea and creatinine change in many diseases such as coronary artery and renal diseases, it is necessary to investigate the acute and chronic effects of aluminum and lead on these biomedical parameters. Methods: A number of 30 New Zealand white rabbits weighted 1350 ± 50g were chosen to investigate the acute and chronic effects of these metals. This study was conducted in vivo, using two different doses, the acute and chronic. To perform the acute stage, aluminum chloride and lead acetate (25 and 13 mg/kg body weight respectively) were injected in to the peritoneum of the rabbits (5 in each group) every other day for two weeks. For the chronic dose, rabbits were administered with aluminum chloride and lead acetate (12.5 and 6.5mg/kg body weight respectively) on alternate days for seven weeks. At the same time deionized water was given to the control groups. Results: Following the acute doses of aluminum and lead salts, plasma concentrations of VLDL, LDL-cholesterol, total cholesterol, triglyceride and sodium were increased significantly, while there were no changes in the plasma levels of HDL-cholesterol, potassium, urea and creatinine. The chronic doses of aluminum and lead salts significantly increased the plasma concentrations of VLDL, LDL-cholesterol, total cholesterol, triglyceride and sodium, but decreased the potassium level. There was no change in the plasma concentrations of HDL, urea and creatinine. Conclusion: Consumption of aluminum and lead are harmful for the body and by increasing the plasma parameters such as VLDL, LDL-cholesterol, total cholesterol, triglyceride and sodium and decreasing potassium may lead to cardiovascular diseases.